B-JLF segmentation-based age-corrected effect sizes from SHARP+MEDI pipelines deemed acceptable in the replication study. - Fahad Salman (6150395) (2025)
Lower values (−1; blue – falsifies the “early rise” hypothesis) represent higher absolute negative effect size and white for effect size of 0. Each vertical panel corresponds to a reference region listed at the top (frontal deep white matter [FDWM]; whole brain [WB]; cerebrospinal fluid [CSF]). Within each panel, each row corresponds to a regularization parameter value used for MEDI inversion algorithm (λD, listed on the left-hand side), while each column represents a regularization parameter value used for SHARP BFR algorithm (λS, listed at the bottom). Significant findings were marked with asterisks (*).